To find the factored form of the quadratic equation and its solutions, we can start with the given quadratic equation:
Part A: Factoring the Quadratic Equation
The quadratic equation given is:
\[ 15x^2 + 13x + 2 = 0 \]
To factor it, we look for two numbers that multiply to \(15 \cdot 2 = 30\) and add to \(13\). The numbers that satisfy this are \(3\) and \(10\).
Now we can rewrite \(13x\) as \(3x + 10x\):
\[ 15x^2 + 3x + 10x + 2 = 0 \]
Next, we group the terms:
\[ (15x^2 + 3x) + (10x + 2) = 0 \]
Factoring each group gives:
\[ 3x(5x + 1) + 2(5x + 1) = 0 \]
Now, we factor out the common factor \( (5x + 1) \):
\[ (3x + 2)(5x + 1) = 0 \]
So, the factored form of the quadratic equation is:
\[ (3x + 2)(5x + 1) = 0 \]
Response for Part A:
(3x + 2)(5x + 1) = 0.
Part B: Finding the Solutions of the Quadratic Equation
Now let's find the solutions using the factored form:
Setting each factor to zero:
-
\( 3x + 2 = 0 \) gives:
\[ 3x = -2 \] \[ x = -\frac{2}{3} \]
-
\( 5x + 1 = 0 \) gives:
\[ 5x = -1 \] \[ x = -\frac{1}{5} \]
Thus, the solutions to the quadratic equation \( 15x^2 + 13x + 2 = 0 \) are:
\[ x = -\frac{2}{3} \quad \text{and} \quad x = -\frac{1}{5} \]
Response for Part B:
x = -2/3 and x = -1/5.
In summary:
- Part A response: (3x + 2)(5x + 1) = 0
- Part B response: x = -2/3 and x = -1/5.